Analysis of The Success of Sipemuda Online E-Government - Devi Andriani, Farah; Haryaningsih, Sri; Yohanes, Yulius; Redha Fachmi Al Qadrie, Syarif (JTP - Jurnal Teknologi Pendidikan, 2024)
This study aims to analyze the success of the Sipemuda Online E-Government system implemented in the Kubu Raya District. As digital transformations continue to shape governance, the Sipemuda platform stands as a prominent example of utilizing technology to enhance public services and administrative efficiency. The research employs a mixed-methods approach, combining quantitative data analysis and qualitative assessments through surveys, interviews, and document analysis. The quantitative aspect of the analysis focuses on key performance indicators (KPIs) such as user adoption rates, transaction volumes, and system uptime. By examining these metrics, the study aims to measure the system's effectiveness in reaching and engaging the target audience. Additionally, data security and privacy concerns are assessed to ensure that citizens' information is adequately protected. On the qualitative front, the research delves into the user experience and satisfaction levels through surveys and interviews with both citizens and government officials. Understanding the perspectives of end-users and administrators provides valuable insights into the strengths and weaknesses of the Sipemuda system. This qualitative analysis also explores any challenges faced during the implementation process and ongoing operation, shedding light on potential areas for improvement. Furthermore, the study investigates the impact of Sipemuda on administrative processes, efficiency gains, and the overall transparency of governance in Kubu Raya District. By analyzing the integration of the e-government system with existing administrative structures, the research aims to identify best practices and areas where further enhancements can be made. The findings of this analysis contribute to the broader discourse on the effectiveness of e-government initiatives in enhancing public services and governance.